Study with β-Glucosidase from Spodoptera frugiperda: Inhibition by Imidazole and Tris, and Dimerization - Chagas, Rafael Siqueira (2024)
This work initially investigated the interaction and inhibition of two usual inhibitors, Imidazole and Tris, on the GH1 β-glucosidase from Spodoptera frugiperda (Sfβgly). In the first chapter, we demonstrated that imidazole reduces the activity of Sfβgly through a partial competitive inhibition mechanism, interacting with the enzyme\'s active site and decreasing substrate affinity. The second chapter shows that Tris acts as a mixed linear inhibitor, forming a nonproductive ESI complex. Both inhibitors can lead to underestimations of kinetic constants in the characterization of GH1 group enzymes. In the third chapter, using site-directed mutations in the enzyme\'s active site pocket, we developed a unified kinetic model that integrates six basic inhibition mechanisms (competitive, non-competitive, and mixed) into a single framework, proposing that these mechanisms are not isolated compartments but rather aspects of the same model. Finally, in the fourth chapter, we investigated the homodimerization of Sfβgly, highlighting that dimer stability is influenced by apolar residues and hydrogen bonds at the interface between the monomers. These findings not only enhance the understanding of oligomerization in GH1 β-glucosidases but also have significant implications for protein design and function.